POPULATION KNOWLEDGE ABOUT THE FAMILY HEALTH PROGRAM IN THE MUNICIPALITY OF IGARASSU - Carlos da Silva, José; Jesus Lima, Maria; Cristiane Leite do Nascimento, Paloma (Health and Society, 2022)
Introduction: The Family Health Program began in mid-1993, and was actually regulated in 1994, as a strategy of the Ministry of Health to change the traditional form of assistance, aiming to stimulate the implementation of a new model of Primary Care that (about 85%) of health problems. Objective: To identify the degree of knowledge of users regarding the services offered in the family health program. Methodology: The study was carried out through exploratory research, cross - sectional, descriptive field and quantitative approach. It was held at USF Beira Mar I, located at Rua Eudes Francisco, numberless, I sea side neighborhood, in the city of Igarassu, state of Pernambuco, Brazil. The sample consisted of 100 users. Results: The data were analyzed manually by filling in the questionnaires used in the interviews. The results were demonstrated through graphs. It was observed that the users of this health unit are mostly well informed of the activities that exist within the health unit. Final Considerations: The Family Health Program has an important role for the health of the population, its importance must be taken to improve care for the population.